Effect of simplified dietary advice on nutritional status and uremic toxins in chronic kidney disease participants - Zarina Ebrahim; Griet Glorieux; M Rafique Moosa; Renée Blaauw (The South African Journal of Clinical Nutrition, 2022)
Background: Traditional chronic kidney disease (CKD) dietary advice is challenging with many restrictions, consequently adherence to the CKD diet is low. Recent literature has proposed less restrictive dietary guidelines in CKD to improve dietary adherence and outcomes; however, limited evidence of its implementation exists. Objectives: This study (trial number: PACTR202002892187265) investigated the effect of simplified dietary advice on nutritional outcomes and adherence after four weeks of dietary advice. Design: A before-and-after study was conducted. Outcome measures: Sociodemographic, clinical and biochemical information was collected and anthropometric measurements performed on Stage 3–5 CKD participants attending a pre-dialysis clinic. Uremic toxins were quantified by UPLC/fluorescence detection. Dietary intake was assessed using a quantified food frequency questionnaire (QFFQ). Participants were educated by the study dietitian on simplified dietary advice using an infographic. A diet-adherence score sheet monitored adherence. All outcomes were measured at baseline and four weeks after the diet was advised. IBM SPSS® version 27 was used for statistical analysis. Results: Fifty-nine participants, mean age 41.0 ± 11.6 years, completed the study. After four weeks, significant improvements were found in body mass index (p < 0.006), waist circumference (p < 0.001), mid-upper arm circumference (P < 0.001), serum total cholesterol (p < 0.045), serum triglycerides (p < 0.017), energy (p < 0.001), protein (p< 0.001) and most dietary intake variables. Overweight and obesity prevalence was high at 68%. Uremic toxin concentrations remained stable. Dietary adherence was 88.6%. Conclusion: The simplified dietary advice suggests improved nutritional outcomes in CKD patients who were predominantly overweight and obese, without compromising kidney function. This study highlights the importance and feasibility of simplified nutrition education in CKD.